Pemberdayaan Pada Ibu Hamil Terhadap Pengetahuan dan Sikap Ibu Mengenai Pemberian ASI Eksklusif - Sabriana, Riska; Riyandani, Rika; Rosmiaty, Rosmiaty (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Breastfeeding is very effective for babies; all their nutritional needs can be met through breast milk. This service activity aims to provide information about the relationship between mothers' knowledge and attitudes toward exclusive breastfeeding. This method uses action research with a participatory action program approach that involves the target community group, namely pregnant women. The result of devotion was an increase in knowledge of 66% and an attitude of 60% after counseling. It can be concluded that this community service provides many benefits for the natural form of targets, namely, the increase in knowledge and attitudes of pregnant women after counseling. Changes in knowledge and attitudes are expected to change behavior in society towards exclusive breastfeeding by applying the knowledge gained in everyday life.